Glycogen synthase kinase 3 beta regulates ethanol consumption and is a risk factor for alcohol dependence. (December 2018) - van der Vaart, Andrew; Meng, Xianfang; Bowers, M.; Batman, Angela; Aliev, Fazil; Farris, Sean; Hill, Jennifer; Green, Thomas; Dick, Danielle; Wolstenholme, Jennifer; Miles, Michael
Abstract Understanding how ethanol actions on brain signal transduction and gene expression lead to excessive consumption and addiction could identify new treatments for alcohol dependence. We previously identified glycogen synthase kinase 3-beta (Gsk3b ) as a member of a highly ethanol-responsive gene network in mouse medial prefrontal cortex (mPFC).Gsk3b has been implicated in dendritic function, synaptic plasticity and behavioral responses to other drugs of abuse. Here, we investigateGsk3b in rodent models of ethanol consumption and as a risk factor for human alcohol dependence.S tereotactic viral vector gene delivery overexpression ofGsk3b in mouse mPFC increased 2-bottle choice ethanol consumption, which was blocked by lithium, a known GSK3B inhibitor. Further, Gsk3b overexpression increased anxiety-like behavior following abstinence from ethanol. Protein or mRNA expression studies followingGsk3b over-expression identified synaptojanin 2, brain-derived neurotrophic factor and the neuropeptide Y Y5 receptor as potential downstream factors altering ethanol behaviors. Rat operant studies showed that selective pharmacologic inhibition of GSK3B with TDZD-8 dose-dependently decreased motivation to self-administer ethanol and sucrose and selectively blocked ethanol relapse-like behavior. In set-based and gene-wise genetic association analysis, aGSK3b -centric gene expression network had significant genetic associations, at a gene and network level, with risk for alcohol dependence in humans. These mutually reinforcing cross-species findings implicate GSK3B in neurobiological mechanisms controlling ethanol consumption, and as both a potential risk factor and therapeutic target for alcohol dependence.